1979
DOI: 10.1007/bf00317643
|View full text |Cite
|
Sign up to set email alerts
|

The limbus spiralis and its relationship to the developing tectorial membrane in the cochlear duct of the guinea pig fetus

Abstract: The development of the interdental cells of the limbus spiralis and of the inner spiral sulcus cells as well as the formation of the mesenchymal teeth of Huschke are described during fetal life up to the day of birth in the guinea pig. Additionally, the changes of the developing tectorial membrane are studied. The ultrastructural observations allow the conclusion that during fetal development at least a considerable part of the material of the tectorial membrane is secreted by the interdental cells of the limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Several secretory-like pits can be observed (asterisks) speculated about possible renewal of TM, and IDCs have been thought to play a crucial role in secreting components into the TM (Iurato 1960;Ishiyama et al 1970). However, the cellular road and secretory trail have remained tentative (Prieto et al 1990;Voldrich 1967;Lim 1969Lim , 1972Thorn et al 1979). In adult animals, the IDCs have been shown to be secretory and the TM was reported to be produced by the IDCs (Prieto et al 1990) and supporting cells in the organ of Corti (Lim and Rueda 1990).…”
Section: Discussionmentioning
confidence: 96%
“…Several secretory-like pits can be observed (asterisks) speculated about possible renewal of TM, and IDCs have been thought to play a crucial role in secreting components into the TM (Iurato 1960;Ishiyama et al 1970). However, the cellular road and secretory trail have remained tentative (Prieto et al 1990;Voldrich 1967;Lim 1969Lim , 1972Thorn et al 1979). In adult animals, the IDCs have been shown to be secretory and the TM was reported to be produced by the IDCs (Prieto et al 1990) and supporting cells in the organ of Corti (Lim and Rueda 1990).…”
Section: Discussionmentioning
confidence: 96%
“…The teeth are separated by furrows filled with the interdental cells. The auditory teeth have long been known by light microscopy (RETzIUs,1884;review by EBNER,1902;FIEANDT and SAXEN,1936;BORGHESAN, 1969) and more recently by transmission electron microscopy (IURATO, 1962;ILBERG, 1968;THORN et al, 1979), but the morphology of the auditory teeth has not been considered in relation to the hearing function of the cochlea. IURATO (1962) demonstrated by polarized light microscopy that the teeth comprised densely packed connective tissue fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission electron microscopy has demonstrated that the interdental cells between the auditory teeth in the spiral limbus of the cochlear duct are bottleshaped; they have a rounded body lying in the interdental furrow, a narrow neck between the upper plates of the teeth, and an apical cytoplasmic sheet lying on the upper surface of the tooth plate under the tectorial membrane; most of each cell is surrounded by the basal lamina and the stroma of the auditory teeth (IURATO, 1962;ILBERG, 1968;ISHIYAMA et al, 1970;LIM,1970;THORN et a!.,1979). It is believed that the smooth surface of the auditory teeth shown by SEM after removal of the interdental cells is the exposed basal lamina, and the contours of the auditory teeth indicate those of the interdental cells or cell cords as follows.…”
Section: Discussionmentioning
confidence: 99%
“…A renewal was earlier proposed in adults [38]and during development [39]. According to Prieto et al, two secretion products could be involved in the turnover of the adult TM and/or secretion of some components.…”
Section: Is the Tectorial Membrane Replenished?mentioning
confidence: 96%